Compliance with the AM+L4776L/CFT International Standard : Lessons from a Cross-Country Analysis - Verdugo Yepes, Concha (IMF Working Papers; Working Paper, 2011)
This paper assesses countries' compliance with the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) international standard during the period 2004 to 2011. We find that overall compliance is low; there is an adverse impact on financial transparency created by the cumulative effects of poor implementation of standards on customer identification; and the current measurements of compliance do not take into account an analysis of ML/FT risk, thereby undermining their credibility and the relevance of some of the policy recommendations taken on their basis. Moreover, we also examine the key role of some cultural, institutional, and financial factors in boosting countries' compliance using econometric analysis.